Responsabilidad escolar y su influencia en el rendimiento académico de los estudiantes del décimo año de educación básica paralelos M - N - L sección vespertina del colegio nacional 9 de Octubre de la ciudad de Machala provincia de El Oro periodo lectivo 2013 - 2014. - Peñafiel Vilela, Nathaly Edith (2015)
So that students have a good academic performance is necessary to achieve meaningful learning this requires highly trained teachers who not only impart class but also contribute to the creation of new methods , materials and techniques , as facilitators of education should also help students educated in values ​​as at the present time human values ​​are being lost and this greatly affects our students.